Smart longline: a tool to help fishermen detect fish and location with smartphone integration - Kamarudin, Kamarudin; Hidayatullah, Muhammad Ragil; Novaris, M. Abizar; Purba, Riska Derliana (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Longline is widely used by fishermen in Indonesia. The use of longlines, which require fishermen to go back and forth periodically to check the catch, creates problems of time and fuel. This research aims to develop a fishing tool for fishermen that will be more efficient in terms of time and fuel. The method used is a literature study related to the components to be used, the design of electrical, mechanical, interfaces and microcontroller programs, as well as the assembly of components and testing tools. The research was conducted from March to July 2022 at the Batam State Polytechnic with the test site at Nongsa Beach, Batam City. The result of this research is a smart longline prototype that can detect fish pulls using accelerometers as vibration detectors on each hook, and locate them using GPS features processed by the Mappi 32 microcontroller using LoRa communication. The information is displayed on the fishermen's smartphones. This allows the fishermen to monitor their catch without having to regularly check the longline. This tool is also equipped with a solar panel as a power source allowing it to operate for 25 hours above sea level. A future proposal for this research includes making a smart longline capable of detecting the species of fish caught. This would help fishermen analyze the species of fish in the water.